PENILAIAN KOMPETENSI KETERAMPILAN BERBASIS PORTOFOLIO PADA PEMBELAJARAN PAI DI MASA PANDEMI COVID-19 - Muhammad Nur Hafidz Afif; Maemoenah (Wahana Islamika Jurnal Studi Keislaman, 2022)
The Covid-19 pandemic that hit Indonesia had a significant impact on all lines of life. Including the world of education who feel it. Teaching and learning activities require to be done remotely/online. Of course, this also affects the components of teaching and learning activities, one of which is assessment. Assessment activities that are usually carried out in the classroom cannot be carried out due to social restrictions. Especially when it comes to skills competency assessment which is usually done with a practical assessment. This study aims to determine the Portfolio-Based Skills Competency Assessment in PAI Learning during the Covid19 Pandemic at SMA UII Yogyakarta. From this study, it can be concluded that the appropriate assessment used to assess skill competency in PAI learning during this pandemic is portfolio-based assessment. This assessment has been carried out by PAI teachers at UII SMA to assess PAI learning in the aspect of skill competence. In its application, the portfoliobased assessment used to assess the competence of PAI learning skills did not find any significant problems.